Intensive Reclamation of Landfills and Polygons for Solid Waste Disposal - Chelnokov, Vitaliy V.; Zabolotnaya, Elena; Matasov, Aleksey V.; Makarova, Anna S.; Glushko, Andrey N. (KnE Life Sciences, 2022)
This research proposed the use of one of the most effective complexons – oxyethylidenediphosphonic acid, namely its derivative compound – phenyldiacetic acid,for the active sorption matrices of humus of mineral origin. The application of active components that stimulate plant growth and photosynthesis processes in hybrid preparations during reclamation were also proposed. Keywords: recultivation of landfill, plant growth stimulation, phytoremediation